Benefit assessment of battery plus solar for customers and the grid. (November 2019) - Boulaire, Fanny; Narimani, Afsaneh; Bell, John; Drogemuller, Robin; Vine, Desley; Buys, Laurie; Walker, Geoffrey
Abstract: A method that can assess the benefit for both the customers and the distribution grid when household or community batteries are installed without central control is presented. An agent-based model is used where the household assets' characteristics and behaviours are modelled and linked to a network model. Electricity data from dwellings on one street in Townsville, Australia, was used to populate the models, and simulations were run under three battery scenarios. The scenarios considered were a) "Business as usual" when no battery storage is installed, b) individual batteries are installed at each household, c) a community battery that would supply all the households is installed. Customer benefits are calculated from the operational costs savings using two types of tariffs available in Queensland. The network assets' health is assessed considering load, current and voltage levels at the distribution transformer. These simulations lead to a better informed decision for the customer, and give the utility insight into how such technologies might impact their assets. Highlights: Agent-based model of electric flows from household circuits to medium voltage network. Integrated analyses through the definition of different models within one framework. Benefit assessment of individual and community batteries for customers and the utility. Customers can make better informed decisions when choosing a battery system. Utility subject to technology uptake can understand and manage better its assets.